Background of Tareeno Dialect’s Proverbs - Khan, Imran (sourcecoder, 2024)
Tareeno is dialect of Pashto language. Which is spoken in Harnai as well as Sharag, Sinjaive, Chawter and Duki. Tareeno dialect has own folklore. But until now it’s not documented. There are many proverbs in tareeno language, which have been collected and discussed with their meanings researcher in Pashto language in this research paper.